2012
DOI: 10.3109/2000656x.2012.697376
|View full text |Cite
|
Sign up to set email alerts
|

Role of the internet in communication between patient and surgeon before rhinoplasty

Abstract: Our aim was to assess the use of the internet for patients considering rhinoplasty, to identify the influence of the medical information acquired, and to review favourable and adverse aspects of the acquired knowledge online. A prospective study was conducted on 106 patients listed for post-traumatic or aesthetic rhinoplasty. We surveyed 18 questions to evaluate demographic and sociological data, and the importance of the information acquired from the internet. Respondents searched online for description of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In fact, patients depend heavily on information found online in general, and this is especially true for health-related information. 33 , 34 With the recent advances in research surrounding BIA-ALCL by the plastic surgery community, a recent analysis of Google and Twitter showed an exponential increase in popularity of searches regarding both BIA-ALCL and BII. 23 This same analysis demonstrated that, unfortunately, misinformation regarding BII is being spread in the process.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients depend heavily on information found online in general, and this is especially true for health-related information. 33 , 34 With the recent advances in research surrounding BIA-ALCL by the plastic surgery community, a recent analysis of Google and Twitter showed an exponential increase in popularity of searches regarding both BIA-ALCL and BII. 23 This same analysis demonstrated that, unfortunately, misinformation regarding BII is being spread in the process.…”
Section: Discussionmentioning
confidence: 99%
“…This new and unique connection tool offers a way to disseminate information to a specific audience in real time. Popular examples include Internet forums, weblogs, and social network sites such as Facebook and Twitter [6-7]. Besides social media, the surge in media coverage through TV reality shows, which are programs that film people doing unscripted activities to entertain the public, has changed the perception of ideal beauty standards [8-9].…”
Section: Introductionmentioning
confidence: 99%
“…Increased reliability of Web site information provides benefits to the practicing surgeon beyond the possibility of increased Web site traffic; better-informed patients are more often satisfied with their results and less likely to be involved in malpractice litigation. [26][27][28] Also, Web site relia-bility and patient trust are associated with the qualifications of the Web site author. Hence it is critical to facilitate access to information on the surgeon's training and board certification status.…”
Section: Discussionmentioning
confidence: 99%
“…Creating Web sites that cater to a larger segment of the population may result in more informed patients, increased Web site traffic, and ultimately an increase in patient knowledge and visits. 26 Though this study is novel in its examination of factors that may stratify Web sites based on a Google search for the keyword "rhinoplasty," it has certain limitations. First, the Google search was conducted in Michigan, which will produce area-specific results.…”
Section: Discussionmentioning
confidence: 99%